Penerapan Inovasi Teknologi Mesin Organic Fertilizer untuk Mewujudkan Konservasi Lingkungan, Kemandirian Petani, dan Pencapaian SDGs Kelompok Tani di Kota Semarang - Irmayanti, Irmayanti; Achmadi, Taofan Ali; Khoiron, Ahmad Mustamil (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
The majority of farmers in Mangunsari Village, Semarang, face crucial problems related to dependence on expensive and soil-damaging chemical fertilizers, compounded by supply scarcity. Despite possessing significant potential in cow livestock waste, its utilization for Organic Fertilizer is hindered by lack of knowledge, skills, and a time-consuming conventional production process (2-3 months). These conditions negatively impact agricultural productivity, production costs, and farmer welfare. This community service program aimed to address these issues through the application of innovative Organic Fertilizer machine technology and farmer empowerment. Implementation methods included problem identification, program socialization, comprehensive training (Organic Fertilizer production using the machine, machine operation, maintenance, and repair, fermentation techniques, product packaging), practical demonstrations, and intensive assistance to Kelompok Tani Teger 1. Program results indicate remarkable success in drastically reducing Organic Fertilizer production time to just 7-14 days with machine use, alongside significant increases in farmer capacity for correctly producing Organic Fertilizer, independently operating and maintaining the machine, and creating product packaging. These achievements effectively decrease reliance on chemical fertilizers, optimize livestock waste utilization, enhance production efficiency, and support farmer independence. This program makes a tangible contribution to environmental conservation, improved farmer economic welfare, and the achievement of SDGs, particularly Zero Hunger (SDG 2) and Decent Work and Economic Growth (SDG 8), through promoting sustainable agriculture.